Propagule Pressure, Habitat Conditions and Clonal Integration Influence the Establishment and Growth of an Invasive Clonal Plant, Alternanthera philoxeroides - You, Wen-Hua; Han, Cui-Min; Fang, Long-Xiang; Du, Dao-Lin (Frontiers in Plant Science, 2016)
Many notorious invasive plants are clonal, spreading mainly by vegetative propagules. Propagule pressure (the number of propagules) may affect the establishment, growth, and thus invasion success of these clonal plants, and such effects may also depend on habitat conditions. To understand how propagule pressure, habitat conditions and clonal integration affect the establishment and growth of the invasive clonal plants, an 8-week greenhouse with an invasive clonal plant, Alternanthera philoxeroides was conducted. High (five fragments) or low (one fragment) propagule pressure was established either in bare soil (open habitat) or dense native vegetation of Jussiaea repens (vegetative habitat), with the stolon connections either severed from or connected to the relatively older ramets. High propagule pressure greatly increased the establishment and growth of A. philoxeroides, especially when it grew in vegetative habitats. Surprisingly, high propagule pressure significantly reduced the growth of individual plants of A. philoxeroides in open habitats, whereas it did not affect the individual growth in vegetative habitats. A shift in the intraspecific interaction on A. philoxeroides from competition in open habitats to facilitation in vegetative habitats may be the main reason. Moreover, clonal integration significantly improved the growth of A. philoxeroides only in open habitats, especially with low propagule pressure, whereas it had no effects on the growth and competitive ability of A. philoxeroides in vegetative habitats, suggesting that clonal integration may be of most important for A. philoxeroides to explore new open space and spread. These findings suggest that propagule pressure may be crucial for the invasion success of A. philoxeroides, and such an effect also depends on habitat conditions.